Chronic pesticide poisoning from persistent low-dose exposures in Ecuadorean floriculture workers: toward validating a low-cost test battery - Breilh Paz y Miño, Jaime Eduardo (2012)
Chronic pesticide poisoning is difficult to detect. We sought to develop a low-cost test battery for settings such as Ecuador’s floriculture industry. First we had to develop a case definition; as with all occupational diseases a case had to have both sufficient effective dose and associated health effects. For the former, using canonical discriminant analysis, we found that adding measures of protection and overall environmental stressors to occupational category and duration of exposure was useful. For the latter, factor analysis suggested three distinct manifestations of pesticide poisoning. We then determined sensitivity and specificity of various combinations of symptoms and simple neurotoxicity tests from the Pentox questionnaire, and found that doing so increased sensitivity and specificity compared to use of acethylcholinesterase alone – the current screening standard. While sensitivity and specificity varied with different case definitions, our results support the development of a low-cost test battery for screening in such settings.